CIRCUMSTELLAR ACTIVITY OF THE HERBIG AE STAR HD163296 - Pogodin, M. A.; Guimaraes, M. M.; Alencar, S. H. P.; Corradi, W. J. B.; Vieira, S. L. A. (Одеські астрономічні публікації, 2007)
We present new results of a high-resolution spectroscopic investigation of the young Ae Herbig star HD163296. Nineteen spectra of this object had been obtained on May 8 - 10, 2002 at the ESO with the FEROS echelle spectrometer installed at the 1.52m telescope. Striking profile variability has been found in a number of lines originating in the stellar wind. Analysis of the variability revealed manifestation of a layered spatial structure of the wind zone containing layers of preferable generation of local inhomogeneities in the outflowing gas. Correlation between different spectral parameters corresponding to infall and outflow gaseous streams evidence in favour of the physical interdependence between the accretion and the mass loss processes in the circumstellar envelope.